Reduced PDZ Interactions of Rescued ΔF508CFTR Increases Its Cell Surface Mobility - Valentine, Cathleen D. (American Society for Biochemistry and Molecular Biology, 2012)
Deletion of phenylalanine 508 (ΔF508) in the cystic fibrosis transmembrane conductance regulator (CFTR) plasma membrane chloride channel is the most common cause of cystic fibrosis (CF). Though several maneuvers can rescue endoplasmic reticulum-retained ΔF508CFTR and promote its trafficking to the plasma membrane, rescued ΔF508CFTR remains susceptible to quality control mechanisms that lead to accelerated endocytosis, ubiquitination, and lysosomal degradation. To investigate the role of scaffold protein interactions in rescued ΔF508CFTR surface instability, the plasma membrane mobility of ΔF508CFTR was measured in live cells by quantum dot single particle tracking. Following rescue by low temperature, chemical correctors, thapsigargin, or overexpression of GRASP55, ΔF508CFTR diffusion was more rapid than that of wild-type CFTR because of reduced interactions with PDZ domain-containing scaffold proteins. Knock-down of the plasma membrane quality control proteins CHIP and Hsc70 partially restored ΔF508CFTR-scaffold association. Quantitative comparisons of CFTR cell surface diffusion and endocytosis kinetics suggested an association between reduced scaffold binding and CFTR internalization. Our surface diffusion measurements in live cells indicate defective scaffold interactions of rescued ΔF508CFTR at the cell surface, which may contribute to its defective peripheral processing.